Implementasi Produk Pegadaian Syariah pada Pegadaian Syariah Cabang Paus Pekanbaru - Anggun Anugrah; Azwar Azwar; Aulia Apriyani Jemmi; Faiqul Halim; Siti Aisyah; Abdul Aziz Hiborohim Srg (SANTRI : Jurnal Ekonomi dan Keuangan Islam, 2026)
This study aims to analyze the implementation of Pegadaian Syariah products at the Paus Pekanbaru Branch based on field observations and interviews. The research focuses on four main products: Rahn, Gold Installments, Gold Savings, and Sharia Business Loans. A qualitative descriptive method was applied using observation, interviews, and documentation as data collection techniques. The findings show that Rahn is the most widely used product because it offers a fast disbursement process, simple procedures, and relatively accessible requirements for customers who need short-term financing. Gold Installments and Gold Savings provide alternative sharia-compliant investment instruments based on real assets, allowing customers to own gold gradually and safely. Meanwhile, Sharia Business Loans play an important role in supporting micro-enterprise development by providing financing that follows Islamic principles. Overall, the implementation of these products reflects Pegadaian Syariah’s contribution to expanding financial inclusion, strengthening public understanding of sharia-based financial services, and providing practical solutions for community economic needs. However, product socialization and customer literacy still need improvement to optimize utilization. This improvement is expected to enhance product acceptance and strengthen sustainable sharia financial service performance.